The Shifting of Alternative Dispute Resolution: from Traditional Form to the Online Dispute Resolution - Latifah, Emmy; Bajrektarevic, Anis H; Imanullah, Moch Najib (Faculty of Law, Universitas Brawijaya, 2019)
The emergence of disruptive technologies has transformed how the conflict is resolved. If Alternative Dispute Resolution (ADR) has been understood as a more efficient method of resolving dispute than through the court, then in line with the development of technologies, Online Dispute Resolution (ODR) considered as the most efficient mechanism in ADR. Through ODR, access barriers are reduced, effectiveness increases, software becomes smarter and some ADR elements are challenged. This article focuses on the shifting of dispute resolution from the traditional approach to the new generation one which called digital justice.